ANALISIS PENYELESAIAN SENGKETA EKONOMI SYARIAH MELALUI BADAN ARBRITASE SYARIAH NASIONAL (BASYARNAS) DAN LITIGASI - Abid Libasuttaqwa Al Kannur, Fauzul; Haniffitriyana, Anggita; Nur Sabrina, Amalia (Penerbit Lafadz Jaya, 2023)
Sharia principles have begun to be rapidly implemented since the existence of Sharia Banks, such as Bank Syariah Indonesia. All activities carried out by Sharia Banks are required to apply sharia principles which are based on Islamic law. All activities carried out by Sharia Banks definitely cause tension. Shooting resolution can be done through litigation or non- litigation. In non-litigation settlement of sharia cases, there is the National Sharia Arbitration Board (BASYARNAS). The purpose of this research is to find out and analyze what benefits are obtained from settlement through Sharia Arbitration and what is the legal certainty in the implementation of Sharia Arbitration execution in Indonesia. This research concluded that by completing settlements through Sharia Arbitration, the parties will gain more benefits compared to litigation settlements. This research also found that there is legal certainty regarding the implementation of Sharia Arbitration decisions as regulated in Supreme Court Regulation (PERMA) Number 14 of 2016 concerning Procedures for Settlement of Sharia Economic Cases which gives permission to Religious Courts to implement Sharia Arbitration decisions.